RETRACTED: The biological functions and related signaling pathways of SPON2 - Zhang, Jingrun; Liu, Ge; Liu, Yuchen; Yang, Pei; Xie, Junyuan; Wei, Xiaowei (Frontiers in Oncology, 2024)
Spondin-2 (SPON2), also referred to as M-spondin or DIL-1, is a member of the extracellular matrix protein family known as Mindin-F-spondin (FS). SPON2 can be used as a broad-spectrum tumor marker for more than a dozen tumors, mainly prostate cancer. Meanwhile, SPON2 is also a potential biomarker for the diagnosis of certain non-tumor diseases. Additionally, SPON2 plays a pivotal role in regulating tumor metastasis and progression. In normal tissues, SPON2 has a variety of biological functions represented by promoting growth and development and cell proliferation. This paper presents a comprehensive overview of the regulatory mechanisms, diagnostic potential as a broad-spectrum biomarker, diverse biological functions, involvement in various signaling pathways, and clinical applications of SPON2.